Early Results From the First Radarsat-I Antarctic Mapping Mission: Proceedings Papers Submitted to International Geoscience and Remote Sensing Society Meeting, Seattle, Washington, July 1998 - Jezek, Kenneth C. (Byrd Polar Research Center, The Ohio State University., 1998)
The Radarsat-1 Antarctic Mapping Mission (RAMP) is a collaborative effort between the Canadian Space Agency and the U.S. National Aeronautics and Space Administration. The major participants in RAMP are The Ohio State University, the Alaska SAR Facility, the Jet Propulsion Laboratory and Vexcel Corporation. The goal of the collaboration is to create the first, complete high-resolution radar mosaic of all of Antarctica for studies of Antarctic glaciology, geology, meteorology and coastal processes. The papers in this report describe early scientific results from the first RAMP Antarctic Imaging Campaign (AIC) which occurred from September to October of 1997. The papers have been accepted for presentation at the July 1998 meeting of the International Geoscience and Remote Sensing Society meeting in Seattle, Washington. Also included is a paper which utilized ERS SAR data to study the geology of the Antarctic Peninsula. Techniques developed in that project will be applied to geologic studies of all of Antarctica. Canadian Space Agency U.S. National Aeronautics and Space Administration (NASA)